Adaptation of Newcastle Disease Virus (NDV) on Vero Cell Line - Ahamed, T.; Hossain, K.M.; Billah, M.M.; Islam, K.M.D.; Ahasan, M.M.; Islam, M.E. (International Journal of Poultry Science, 2004)
Newcastle disease virus (NDV) is the infectious agent of Newcastle disease in poultry. This virus can grow within different animal cells including primary cell culture and established cell line. In order to adapt NDV on African green monkey kidney (Vero) cell line, five consecutive passages were done. Eagle`s minimum essential medium (EMEM) with supplements was used for both culturing Vero cells and maintaining NDV on Vero cells. During first and second passage, wild NDV didn`t produce any clear evidence of cytopathic effect (CPE), but in third passage changes in the characteristics of cell monolayer were observed. During fourth and fifth passages, clear and consistent CPE were observed within 50 to 60 hours of infection. CPE was characterized by formation of syncytium, giant cell, dendritic-shaped cell and finally plaque. The titer of passage 5 (P5) virus was 10-3.9TCID50, whose purity was tested by serum neutralization test (SNT) and the result was 1.6 x 104 units/ml.